Paradoxical Platelet Activation Was not Observed on Dissociation of Abciximab from GPIIb-IIIa Complexes - Ndoko, Serge; Poujol, Christel; Combrié, Robert; Nurden, Alan; Nurden, Paquita (Thrombosis and Haemostasis, 2002)
The ability of abciximab to bind and dissociate from platelets raises the question of the conformational state of GPIIb-IIIa complexes losing abciximab and the risk of paradoxical drug-induced platelet activation. Platelets incubated with abciximab and mixed in vitro with c7E3 Fab-free platelets lost the drug to the new platelets giving a single platelet population with a unimodal abciximab distribution within 17 h. Prelabeling the receiving platelets with phycoerythrin-labeled anti-GPIb monoclonal antibody (MoAb), permitted their identification by flow cytometry. Binding of PAC-1 and AP6, two MoAbs specific for activated GPIIb-IIIa, was then assessed to both losing and receiving platelet populations during transfer of abciximab. The subpopulation losing c7E3 Fab failed to show increased binding of these MoAbs. However, PAC-1 binding increased in both subpopulations after addition of ADP. Thus GPIIb-IIIa complexes are not in an activated state after dissociation of abciximab unless there is an additional source of activation.
Keywords: Platelet activation; GPIIb-IIIa complex; abciximab; antithrombotic therapy